Tinjauan Yuridis Harta Warisan Yang Dialihkan Oleh Salah Seorang Ahli Waris Tanpa Persetujuan Ahli Waris Yang Lain (Studi pada Pengadilan Agama Kelas II Baubau) - Husnul Khotima Wardhani Slamet (Jurnal Ilmu Hukum Kanturuna Wolio, 2021)
The purpose of the study os to determine the position of inheritance that has been transferred by heirs without the consent of other heirs while the method used in this study is a type of normative legal research, which is aprocess of finding legal rules, legal principles, and doctrines, legal doctrine in order to answer legal issues faced which pruduce new arguments, theories and concepts as prescription in solving problem faced. The results of the study are the position of property rights as inherited property that has been traded by heirs without the consent of the other heirs according to Article 1230 of the Civil Code regarding the requirements for the validity of a sale and purchase agreement and 1471 KUH Civil law regarding buying and selling, which is implicit requires that the seller must be the owner of the goods sold or the legitimate holder of land right, meaning that the seller has the right to sell the land that is the object of sale and purchase by unauthorized people is null and void meaning that from the beginning the law never there was a sale and purchase thus the rights to the land purchased from the seller never changed even though the buyer had controlled the land. The law arising from the transfer of inheritance without the consent of other heirs is that other heirs can sue the court so that the lans is included in the inheritance that will be divided, and the sale and purchase of landbased on Article 1471 of the Civil Code is canceled. With the cancellation of the sale an purchase, the sale and purchase is deemed to have never existed, and each party returned to its original state before the “sale and purchase” event, in which the ownership of the land remained with the heirs and case objects sold without consent from them, cam make a civil suit on the basis of an act against the law, as stipulated in article 1365 of the Civil Code.